CLINICAL CASE SURGICALTREATMENT OF IATROGENIC BILE DUCT INJURY USING PERCUTANEOUS MINIMALLY INVASIVE TECHNOLOGIES - E. V. Tokarenko; A. V. Andreev; V. M. Durleshter; V. D. Sahno; A. A. Kulakov; A. U. Barannikov (Кубанский научный медицинский вестник, 2016)
The article presents a clinical case with iatrogenic injury to the common bile duct after laparoscopic cholecystectomy and surgical treatment with the use of minimally invasive percutaneous techniques. The patient was admitted to the regional clinical hospital №2 of Krasnodar with iatrogenic injury to the common bile duct at ( 11 Bismush or (+1) Halperin), on the 3rd day after operation. Patient's health was hard, marked clinical manifestations a mechanical icterus syndrome and sys-temic inflammatory response syndrome. The patient performed ultrasound diagnosis of ab-dominal organs, laboratory blood tests. Patients showed signs of bile hypertension. We did per-cutaneous drainage of the bile ducts under the control of radiological methods as preoperative period. After 2 months, the patient made a planned reconstructive surgery - biliodigestive anas-tomosis Roux. There were not complications in the postoperative period. Literature review and difficulties of timely diagnosis, examination and minimally invasive treatment of these patients are showed.